Development of Sense of Coherence Promoting Program Using Empowerment Process with Family Support for Older Adult Muslims with Chronic Kidney Disease Undergoing Hemodialysis - Seemun, Porntip; Komjakraphan, Patcharee; Jittanoon, Piyanuch (Journal of Research in Nursing-Midwifery and Health Sciences, 2020)
This study aims to develop of the sense of coherence promoting program using empowerment process with family support by applying the concept of empowerment family support, and sense of coherence of Antonovsky. The program development process was divided into two phases 1) program development, and 2) program evaluation. The results of the study showed that the program consisted of four activities; 1) accepting and understanding the problem 2) enhancing strength by family 3) solving the problems together and 4) home visit. The program was tested for content validity by three experts resulting in a CVI of 0.8. The experts suggested that the program should emphasize participations of family activities. The feasibility assessment of the program was tested by three nephrology nurses who work in hemodialysis unit. The results found that all of these nurses reported that the program was practical. Thus, the program should be tested for effectiveness by conducting further experimental research in older adult Muslims with chronic kidney disease receiving hemodialysis.